A little labeling goes a long way: Semi‐supervised learning in infancy. Issue 1 (18th September 2018) - LaTourrette, Alexander; Waxman, Sandra R.
Abstract: There is considerable evidence that labeling supports infants' object categorization. Yet in daily life, most of the category exemplars that infants encounter will remain unlabeled. Inspired by recent evidence from machine learning, we propose that infants successfully exploit this sparsely labeled input through "semi‐supervised learning." Providing only a few labeled exemplars leads infants to initiate the process of categorization, after which they can integrate all subsequent exemplars, labeled or unlabeled, into their evolving category representations. Using a classic novelty preference task, we introduced 2‐year‐old infants ( n = 96) to a novel object category, varying whether and when its exemplars were labeled. Infants were equally successful whether all exemplars were labeled (fully supervised condition) or only the first two exemplars were labeled (semi‐supervised condition), but they failed when no exemplars were labeled (unsupervised condition). Furthermore, the timing of the labeling mattered: when the labeled exemplars were provided at the end, rather than the beginning, of familiarization (reversed semi‐supervised condition), infants failed to learn the category. This provides the first evidence of semi‐supervised learning in infancy, revealing that infants excel at learning from exactly the kind of input that they typically receive in acquiring real‐world categories and their names. Abstract : Two‐year‐old infants successfully engage in semi‐supervised learning, integrating labeled and unlabeled exemplars to acquire new object categories. Infants in a semi‐supervised condition, who heard only the first two exemplars labeled, categorized as successfully as infants who heard all exemplars labeled. Infants' successful semi‐supervised learning reveals a mechanism by which they learn novel categories when labeled exemplars are rare.